PERSEPSI MASYARAKAT TERHADAP KEBERADAAN LUTUNG JAWA (Trachypithecus auratus) DI HUTAN RAKYAT PAMOYANAN KECAMATAN CIBINONG KABUPATEN CIANJUR - Srimulyaningsih, Reni; Nursyamsie, Nucky (JURNAL RIMBA LESTARI, 2023)
Javan langur (Trachypithecus auratus) is one of the protected animals. So far, the Javanese langur's habitat includes primary forest, secondary forest, coastal forest, mangrove forest and tropical rainforest. However, currently based on information from the community, there are groups of Javanese langurs that have left the natural forest, one of which is the community forest. The object of research is to know of community's knowledge about the existence of Javanese langur in the community forest, the community's perception of the existence of Javanese langur in the community forest and the relationship between knowledge and community perception of the existence of Javanese langur in the community forest, Pamoyanan Village, Cibinong District, Cianjur Regency, West Java. The data collected included interviews using closed questionnaires. The analysis data by SPSS 25 followed by a correlation test with a confidence level of 0.05. The result of research is that public knowledge has the highest frequency of 46 respondents with a percentage of 76.7% in the good category. The public's perception that the frequency and the highest percentage got 54 respondents with a percentage of 90% in the good category, therefore, the public's presentation of Javanese langur is good. The correlation of knowledge and perception of the community as a whole with a sample of 60 people about the existence of Javanese langur has a sig value of 0.00 which means there is a correlation or there is a strong relationship or a strong correlation.